2013
DOI: 10.1186/1752-153x-7-78
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 1, 3-dihydroxyxanthone mannich base derivatives as anticholinesterase agents

Abstract: BackgroundAlzheimer’s disease (AD), a progressive and degenerative disorder, has become one of the severe problems among the aged population all over the world. To use cholinesterase inhibitor drugs has become the most predominant treatment strategy for AD.ResultsA series of novel 1, 3-dihydroxyxanthone Mannich bases derivatives (1a ~ 4e) were synthesized, structure elucidated and evaluated for anti-cholinesterase activity. The result showed that most of the target compounds exhibited moderate to good inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 44 publications
(40 reference statements)
4
19
0
Order By: Relevance
“…Natural flavonoids such as genistein derivatives [32], indole alkaloids [33,34], prenylated xanthones [35], and triterpenoids [36] have been reported to inhibit ChE. In our experiments, the mixed-type inhibitory mechanisms of our isolated compounds (4, 8, 13, and 15) are similar to the enzyme inhibitors above [28,29]. This is shown by the fact that our compounds not only compete with the substrate in the active site pocket, but can also bind to the enzyme-substrate complex.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Natural flavonoids such as genistein derivatives [32], indole alkaloids [33,34], prenylated xanthones [35], and triterpenoids [36] have been reported to inhibit ChE. In our experiments, the mixed-type inhibitory mechanisms of our isolated compounds (4, 8, 13, and 15) are similar to the enzyme inhibitors above [28,29]. This is shown by the fact that our compounds not only compete with the substrate in the active site pocket, but can also bind to the enzyme-substrate complex.…”
Section: Resultssupporting
confidence: 72%
“…Loss of cholinergic cells, particularly in the basal forebrain, is accompanied by loss of the neurotransmitter acetylcholine [25,26]. One approach is to inactivate AChE, the enzyme that 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 one was identified as an AChE mixed-type inhibitor, and molecular docking studies suggested that it was most likely to bind to the active site and the peripheral anionic site of ChE [29]. Interestingly, although there have been a number of reports on the design and development of synthetic AChE inhibitors, several studies have discussed AChE inhibitors derived from plants [30,31].…”
Section: Resultsmentioning
confidence: 97%
“…Inhibitory activity against AChE and BuChE of phenolic Mannich bases 58 (R 1 ¼ H, CH 3 , allyl, prenyl; NR 2 ¼ N(CH 3 ) 2 , N(C 2 H 5 ) 2 , 1pyrrolidinyl, 1-piperidinyl, 4-morpholinyl) of xanthone derivatives ( Fig. 10) was found to be moderate to good compared to that of reference drug galantamine [467]. Candidates 58 derived from diethylamine as amine reagent in the Mannich reaction were generally the most potent inhibitors of both enzymes.…”
Section: Inhibitors Of Cholinesterasesmentioning
confidence: 99%
“…For compound 2, the K m value of the enzyme with and without inhibitor remained the same (100 lM) whereas the V max value decreased, which indicated a non-competitive inhibition of AChE. It has been observed that substitution of hydroxyl, methoxyl, allyloxy and prenylated oxyl at the C-3 position in the xanthone skeleton with a methoxyl group at the C-3 position was the most effective in inhibiting AChE [35]. This supported the inhibitory properties of both compounds 1 and 2 which possessed a methoxyl group at the C-3 position.…”
Section: Evaluation Of Inhibition Mechanism and Kinetics Of Ache Maomentioning
confidence: 97%